Outsourced contracts, buyer-supplier trust, supplier opportunistic behavior and supplier performance in ugandan public procuring and disposing entities (PDEs) - Ahimbisibwe, Arthur; Muhwezi, Moses; Nangoli, Sudi (Journal of Public Procurement, 2021)
This study sought to examine the extent to which outsourced contracts, buyer-supplier trust and supplier opportunistic behavior explain supplier performance in Ugandan Public Procuring and Disposing Entities (PDEs). This study was prompted by reports of long lead times, failure to match specifications, late deliveries, poor quality of services delivered, contract violations, and increased supplier cheating. Cross sectional data from 116 central government PDEs concerning outsourced contracts was collected using a self-administered questionnaire. Hierarchical regression was used to indicate what happens to a model that was developed as part of this research as different predictor variables are introduced. The findings revealed that outsourced contracts, buyer-supplier trust, and supplier opportunistic behavior are significant predictors of supplier performance. The study has both managerial and policy implications which are discussed in this paper.
Keywords: Outsourced contracts; Buyer-supplier trust; Supplier opportunistic behavior; Ugandan public procuring; Disposing entities (PDEs)